Genealogy of a Statistical Evidence: from the “Economic Success” of Late Colonialism to the “Failure” of the African States (ca1930-ca1980) - (:unkn) unknown (My University, 2015)
In the early 1980s, the acknowledged economic failure of the African States, which is statistically verifiable thanks to poor growth figures, came alongside the liberal reforms implemented in Africa under the auspices of international financial institutions: the failure appeared all the more obvious given that many African States had moved from strong growth at the end of the colonial period to stagnation in the 1960s and recession in the 1970s. This article aims to display the origins of this statistical evidence that has emerged in the context of a liberal turn. It traces the history of growth figures in Africa considering the actual conditions under which they have been compiled by statisticians, their successive meanings and their different uses by the contemporaries. It shows that the statistical great narratives ruling on the failures in the African States implied reusing figures that were considered as uncertain at early stages of development and changing the meaning of these figures: since the late colonial period, these figures continuously provided conflicting interpretations and several reinterpretations, before formalizing the failure of the African States and the need for liberal reforms in the early 1980s. In the end, statistics appears not only as a technique of government and legitimization, but also as one means by which different eras can project into each other by conferring present meaning to past – or future – figures.
Keywords: African Research